Association of HLA class II genes with susceptibility to Crohn's disease. (July 1996) - Danzé, P M; Colombel, J F; Jacquot, S; Loste, M N; Heresbach, D; Ategbo, S; Khamassi, S; Périchon, B; Semana, G; Charron, D; Cézard, J P
Abstract : BACKGROUND: Published studies on the association between HLA class II genes and inflammatory bowel disease are contradictory perhaps because of the limited size and ethnic heterogeneity of the populations studied. AIM: To compare the frequencies of HLA class II genes in a large number of French patients with Crohn's disease and in an ethnically matched control group. METHODS: 344 patients (196 F, 148 M, mean age 23.6 years) with Crohn's disease were molecularly genotyped for the HLA-DQB1 and DRB1 alleles. The results were compared with those for an ethnically matched control population of 488 white adults. RESULTS: There were two significant variations of alleles at the DQB1 locus: an increase in DQB1*0501 allele frequency (chi 2 = 10.6, corrected p value (pc) = 0.01, odds ratio (OR) = 1.61) and a decrease in DQB1*0602/0603 allele frequencies (chi 2 = 8.43, pc = 0.037, OR = 0.66). DRB1 analysis showed associations with three allelic variations: an increase in the frequencies of DRB1*01 (chi 2 = 12.86, pc = 0.003, OR = 1.75) and DRB1*07 alleles (chi 2 = 11.18, pc = 0.008, OR = 1.58) and a very significant decrease in that of the DRB1*03 allele (chi 2 = 19.7, pc = 9.10(-5), OR = 0.46). CONCLUSION: The alleles DRB1*01 and DRB1*07 are associated with susceptibility to Crohn's disease. The strong negative association between the DRB1*03 allele and Crohn's disease suggests that the HLA-DRB1*03 allele mediates 'resistance' to Crohn's disease.